2018
DOI: 10.1093/cvr/cvy112
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and increased endothelial mechanical stretch promote monocyte differentiation and activation: roles of STAT3, interleukin 6 and hydrogen peroxide

Abstract: AimsMonocytes play an important role in hypertension. Circulating monocytes in humans exist as classical, intermediate, and non-classical forms. Monocyte differentiation can be influenced by the endothelium, which in turn is activated in hypertension by mechanical stretch. We sought to examine the role of increased endothelial stretch and hypertension on monocyte phenotype and function.Methods and resultsHuman monocytes were cultured with confluent human aortic endothelial cells undergoing either 5% or 10% cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 66 publications
2
92
1
3
Order By: Relevance
“…This is in line with earlier observations that T cell activation and vascular recruitment depend on pressure increase and are in part dependent on mechanical stretch, 11 which involves and affects antigen presenting cell activation. 29 Taking into account that miR-214 increases in T cells upon activation and perivascular T cell infiltration increases 3-to 4-fold in hypertension, T cell infiltration into PVAT may provide the most compelling mechanism of miR-214 increase in this compartment in Ang II-induced hypertension. Moreover, miR-214 seems to regulate T cell activation characterized by profibrotic effector cytokine production and chemokine receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with earlier observations that T cell activation and vascular recruitment depend on pressure increase and are in part dependent on mechanical stretch, 11 which involves and affects antigen presenting cell activation. 29 Taking into account that miR-214 increases in T cells upon activation and perivascular T cell infiltration increases 3-to 4-fold in hypertension, T cell infiltration into PVAT may provide the most compelling mechanism of miR-214 increase in this compartment in Ang II-induced hypertension. Moreover, miR-214 seems to regulate T cell activation characterized by profibrotic effector cytokine production and chemokine receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism linking hypertension and COVID-19 is the immune system, which is dysregulated in hypertension and SARS-CoV-2 infection. 39,40 Poor control of blood pressure may contribute to further dysregulation of the immune system. For example, it has been shown that hypertension, in humans, is associated with circulating lymphocyte counts, 41 and CD8þ T cell dysfunction is observed in patients with hypertension 42 .…”
Section: Covid-19 and Hypertensionmentioning
confidence: 99%
“…101 It has been observed that increased stretch of hypertensive arteries activates endothelium, releasing IL-6, IL-23 and ROS whilst reducing nitric oxide (NO), and favouring STAT3 activation. 100 Studies have also showed that isoketals (or isolevuglandins, derived from free radical-mediated lipid peroxidation) accumulate in DCs in hypertension, promoting cytokine production and being able to act as neoantigens when adducted to proteins, activating DCs. 98,99 These isoketalmodified proteins have been found to be elevated in circulating monocytes and DCs from hypertensive patients.…”
Section: Hypertensionmentioning
confidence: 99%